Gas flow rate control using magnetic fluid - Haruhiko YAMASAKI; Hiroshi YAMAGUCHI (Nihon Kikai Gakkai ronbunshu, 2015)
A novel method of controlling gas flow rate using magnetic fluid is proposed. Magnetic fluids under non-uniform magnetic field have strong dynamic pressure distribution along the magnetic field gradient at the gas-liquid interface with bulk magnetic body force. The principle of proposed gas flow rate control technique is based on controlling the pressure distribution, which can be controlled by magnetic field. In this report, controlling technique is introduced and the accuracy of the flow rate control with resolution of the control technique is reported. From measured data (giving a reference for measuring the small gas flow rate), it was found that the flow rate decreases with increasing magnetic flux intensity, and is largely dependent on the magnetic pressure which acts on magnetic fluid, particularly to the interface of gas-liquid phase. The flow rate and the magnetic pressure have a definite relation with the flow coefficient, so that, the flow rate can be controlled only by the magnetic pressure. It was satisfactory verified from the proposed controlling technique that the proposed gas flow controlling method is useful to control the low gas flow rate as low as 0.3×10-5m3/s with the excellent resolution.